Student's Perception on Walkability Performance of Campus Facilities: a Case study of UiTM Perak, Seri Iskandar Campus - Yuserriea, Farid Al Hakeem; Sayed AbulKhair, Sayed Muhammad Aiman; Azman, Muhamad Azrul Azwan; Wan Omar, Wan Rabiah (School of Social Sciences, USM, 2017)
This study is trying to investigate the perceptions of student in term of walkability performances of campus facilities in UiTM Perak, Seri Iskandar Campus. For the past few years, UiTM Perak has been promoting "Experiential Learning in A Green Environment". One of the main component to achieve green environment is walkability. Walking has been a part of an everyday routine for students in Malaysian universities. Almost every university in Malaysia is built in a complex compound. Therefore, walking is a must for moving from one point to another. Walking as mode of transportation will promote good health and a sustainable environment. The pedestrian and walkway seem to be lacking and not well maintained. This has been an issue for the students who live in the campus, when they need to walk from their residential block to their academic block as they tend to walk on the street rather than on the pedestrian. This study incorporates two methodologies, based on quantitative and qualitative method to justify this situation. Data collected via questionnaires from 200 students of UiTM Perak, Seri Iskandar Campus who reside on campus. For qualitative method, a visual study was conducted to study in terms of visual perception. This study is expected to give a clear perspective to the university regarding the problems and what needs to be done for the future development of the built environment.